Microelectrode fabrication using Indium Tin Oxide (ITO) for microfluidic devices employing dielectrophoresis - Kadri, Nahrizul Adib; Hoettges, K.F.; Hughes, M.P. (2008)
Dielectrophoresis (DEP) has been widely employed as one of the techniques in developing various micro-electromechanical systems (MEMS). The manipulation of particles using DEP forces is dependent upon the particles' dipole moment that is produced in the presence of an electric field gradient. The paper documents the fabrication processes employed at the University of Surrey in developing the microelectrodes to be used in generating the said field gradient. Â© 2008 Springer-Verlag.